Just so stories for little children - Kipling, Rudyard, 1865-1936. (New York : Weathervane Books : distributed by Crown Publishers, 1978)
Twelve stories about animals, insects, and other subjects include "How the Camel Got His Hump." "The Butterfly That Stamped," and "How the Alphabet Was Made."
Reprint of the 1902 ed. published by McMillan, London.
1190
Keywords: Children's stories, English; Animals -- Fiction; Short stories